2023
DOI: 10.3390/rs15194805
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Transmission Towers’ Foundation Ground Subsidence in the Salt Lake Area Based on Multi-Temporal Interferometric Synthetic Aperture Radar and Deep Learning

Bijing Jin,
Taorui Zeng,
Taohui Yang
et al.

Abstract: Displacement prediction of transmission towers is essential for the early warning of transmission network deformation. However, there is still a lack of prediction on the ground subsidence of the tower foundation. In this study, we first used the multi-temporal interferometric synthetic aperture radar (MT-InSAR) approach to acquire time series deformation for the transmission lines in the Salt Lake area. Based on the K-shape clustering method and field investigation results, towers #95 and #151 with representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Based on the findings above, it has been shown that topography, a fundamental element of natural circumstances, influences the dispersion of regional hydrothermal The second module was LSTM layers, which extract relevant vectors for constructing time series [50]. The LSTM model is a variant of the Recurrent Neural Network (RNN) specifically designed to tackle managing long-term dependencies.…”
Section: Spatial Distribution Patternsmentioning
confidence: 99%
“…Based on the findings above, it has been shown that topography, a fundamental element of natural circumstances, influences the dispersion of regional hydrothermal The second module was LSTM layers, which extract relevant vectors for constructing time series [50]. The LSTM model is a variant of the Recurrent Neural Network (RNN) specifically designed to tackle managing long-term dependencies.…”
Section: Spatial Distribution Patternsmentioning
confidence: 99%